2019
DOI: 10.1515/geo-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Subsurface Temperature Modeling beneath Mt. Lawu and Mt. Muriah in The Northeast Java Basin, Indonesia

Abstract: The subsurface temperature has many impacts on geological phenomena such as hydrocarbon generation, geothermal energy, mineralization, and geological hazards. The Northeast Java Basin has various interesting phenomena, such as many oil fields, active faults, mud eruptions, and some active and dormant volcanoes. We measured temperature data from tens of wells along a 130 km survey line with an average spacing of 5 km. We also measured the thermal conductivity of rocks of various lithologies along the survey lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…From its peak, erosion has occurred. A 2019 study on geothermal flows shows that Mount Lawu is still active today [21]. Evidence of the eruption of Mount Lawu can be seen in Figure 1.…”
Section: Time and Locationmentioning
confidence: 99%
“…From its peak, erosion has occurred. A 2019 study on geothermal flows shows that Mount Lawu is still active today [21]. Evidence of the eruption of Mount Lawu can be seen in Figure 1.…”
Section: Time and Locationmentioning
confidence: 99%
“…This river has a length of 234 km, with a width about 3,656.78 km 2 . This river flows east to west between the Kudus, Pati and Rembang Hills to the north and the Kendeng Hills to the south [34,35]. The geographic area of the study area is shown in We use sample fossil of a deer (Cervidae) and 3 sediments sample from outcrops around sampling area.…”
Section: Geological Settingmentioning
confidence: 99%
“…[1]- [5]. There are some possibilities in the uniqueness of the Indonesian carbonate characteristics, especially in Java, due to high geothermal heat flow which produced by either volcanism activity or fault activity, see [6] This research may reveal the uniqueness of Indonesian carbonate due to the CO2 injection characteristics.…”
Section: Introductionmentioning
confidence: 99%